Microwave metamaterial-based superlens for energy focusing applications - Thang , Kieu Vu; Tung, Nguyen Thanh; Janssens, Ewald (Vietnam Journal of Science and Technology, 2018)
Superlens imaging has been known as one of the most intriguing applications of metamaterials due to its capability of sub-wavelength imaging. In this report, we numerically demonstrate the possibility to make an amplifying superlens, which can focus and consequently enhance electromagnetic signals emitted at GHz frequencies. Simulations using the finite integration technique are performed to explore the amplifying mechanism of the proposed superlens. It is found that the focused signals can be considerably intensified at a selected position. The results show potential uses of metamaterial superlenses for future wireless energy transfer devices and novel energy harvesting applications.